Using Lopinavir Concentrations in Hair Samples to Assess Treatment Outcomes on Second-Line Regimens among Asian Children - Wasana Prasitsuebsai (2018)
© 2015, Mary Ann Liebert, Inc. We conducted a prospective monitoring study to determine whether antiretroviral (ARV) levels in hair of Asian children on second-line protease inhibitor-based ARV therapy (ART) are associated with virologic failure (VF), compared to plasma drug levels and self-reported adherence. HIV-infected Asian children on second-line ART regimens were enrolled into a longitudinal cohort. Traditional adherence measures, plasma, and hair samples were collected 24 weeks after study enrollment. Hair ARV levels were determined via liquid chromatography/tandem mass spectrometry. Among 149 children on lopinavir/ritonavir-based regimens, 47% were female; the median [interquartile range (IQR)] age was 10.3 (7.9-13.3) years. The median CD4% was 26% (IQR 21.7-32.1%) and the median CD4 cell count 754 (IQR 596-1,013) cells/mm3. The median duration of lopinavir-based ART prior to week 24 of the study was 2.9 (IQR 1.6-4.2) years. Adherence was >95% in 91% (135/148) by visual analogue scale and 89% (129/145) by pill count. The median lopinavir hair concentrations were 5.43 (IQR 3.21-9.01) ng/mg in children with HIV RNA >1,000 copies/ml and 9.96 (IQR 6.51-12.31) ng/mg in children with HIV RNA <1,000 copies/ml (p = 0.003). Plasma trough and lopinavir hair concentrations were not statistically significantly correlated (Pearson's correlation coefficient 0.20; p = 0.13). Increasing lopinavir hair concentrations in quartiles were strongly associated with virologic success (odds ratios ≥4.0, overall p = 0.02), while self-reported adherence, pill count, and plasma lopinavir levels were not. Based on this first report of hair ARV concentrations and virologic outcomes in children, ARV hair concentrations, representing longer-term adherence, may be useful to identify children at risk for VF.